GAMBARAN MUTU PELAYANAN KESEHATAN PADA PASIEN RAWAT INAP DI RSUD M. NATSIR SOLOK TAHUN 2021 - ELVIRA JULITA; ERPIDAWATI ERPIDAWATI; SILVIA ADI PUTRI (JURNAL ILMIAH SIMANTEK, 2023)
Based on the observations of the author are done in RS M. Natsir Solok year 2020 is seen that the dimensions of the quality of health services has been running well malaupun there are still some yet to be done with a good as dimensions of the quality of empaty. The purpose of research to determine the picture quality of health services on an inpatient in a Hospital M. Natsir Solok. This research was conducted quantitatively, the collection of data by koesioner and instrument of data collection used in this research is koesioner. The number of samples ebanyak 30 respondents.The results of the research dimensions of service quality from the 30 respondents said the quality of the Reliability of respondents who said the good as stated that more than half good (7%), and less than half good (23%), the quality of the Responsiveness of respondents who said the good as stated that more than half good (70%), and less than half good 30%, quality Assurance of respondents who said the good as stated that more than half good 77%, and less than half good 23%, the quality of Empaty respondents who said the good as stated that more than half good (67%) and less than half good 33%, the quality of the Tangible respondents who said the good as stated that more than half good 70%, and less than half good 70%.It is concluded that the quality of health services on an inpatient Surgical and Neorologi RSUD M. Natsir Solok of the 30 respondents most of the respondents feel good with a score of 72%, and respondents who feel less well with a score of 28% to service patients hospitalized surgical and neorologi in RS M. Natsir Solok.